2021
DOI: 10.21203/rs.3.rs-510164/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation Cover Change and Its Diversity in Urban Areas of Medan

Abstract: Vegetation plays an important role in maintaining the environmental quality of urban areas. Increase in population and development of cities has led to land conversion with lesser vegetated areas. Land cover change analysis in urban areas is needed, especially for urban regional planning with green open space consideration. This research was conducted to analyze urban vegetation cover and its changes in two sub-districts of Medan between the years 1999 and 2019. Normalized difference vegetation index (NDVI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Higher values of the NDVI index indicate higher vegetation density [67,68]. The model XGBoost MNDWI is a more sensitive index than NDWI for estimating SMC, similar to results achieved in other studies [69].…”
Section: Discussionsupporting
confidence: 86%
“…Higher values of the NDVI index indicate higher vegetation density [67,68]. The model XGBoost MNDWI is a more sensitive index than NDWI for estimating SMC, similar to results achieved in other studies [69].…”
Section: Discussionsupporting
confidence: 86%
“…The Kucur Resort is dominated by areas with NDVI values of 0.0 -0.5 (Table 3). It is revealed that the most of Kucur resort areas indicate a fairly dense canopy as described by Zaitunah et al [18]. All Javan Langur encounter points were distributed in medium vegetation density areas (Fig.…”
Section: Ndvisupporting
confidence: 60%
“…Most orangutans' daily activities in their natural habitats, such as swinging from one branch to another branch, climbing, and hanging, are highly dependent on trees. Orangutans also build a new nest every day near a food source and quite high above the ground [61,[76][77][78]. The abundance of feed is a necessity for orangutans as they consume around 6.2 kg of food/day/individual [79].…”
Section: Ensuring Orangutan Welfarementioning
confidence: 99%